(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the relationship between hemoglobin levels and the severity of left ventricular dysfunction in pediatric heart failure, informing personalized therapeutic strategies. Study Design: A retrospective study Place and Duration of Study: This study was conducted at the Department of pediatrics cardiology Lady Reading Hospital Peshawar between December 2022 and December 2023. Methods: Haemoglobin levels and the degree of left ventricular dysfunction were evaluated in a retrospective obsdrvational study of paediatric heart failure patients at Lady Reading Hospital in Peshawar. Results: In 684 patients, a higher degree of left ventricular dysfunction was linked with lower haemoglobin levels. There were 310 (45.3%) females and 374 (54.7%) males, almost evenly distributed by gender. The average age was 6.8 years. Haemoglobin levels averaged 11.7 g/dL (SD = 1.2) for mild cases, 11.4 g/dL (SD = 1.3) for moderate cases, and 10.8 g/dL (SD = 1.4) for severe cases, depending on the severity of left ventricular dysfunction. Conclusion: In conclusion, hemoglobin levels in pediatric heart failure indicate promise as prognostic markers, indicating the need for more research to develop customised therapies and enhance results.